Population growths, Job growths and Commuting flows in Perth - Anderson, J; Byles, D; Johnson, L (Perth, 2010)
This paper represents the first case study of a broader research project which will identify recent spatial changes in employment and residential population within Australia’s five largest cities and investigate how commuting behaviour has responded to those changes. Understanding changes in the spatial patterns of major city land uses will assist in the development of urban, infrastructure and local government policy. The primary aim of this study is to identify spatial changes in population, employment and commuting in Perth, with a view to providing a solid evidence base about the reality of the trends that have been shaping the city in recent years. A secondary aim is to investigate the extent to which metropolitan plans have been successful in attempting to mould the city’s spatial distribution of population, employment and commuting.
Bureau of Infrastructure and Transport and Regional Economics
Keywords: Housing, communities and neighbourhoods; Labour market; Housing, communities and neighbourhoods; Employment and unemployment